2009
DOI: 10.1002/sce.20350
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a school–aquarium collaboration: An intersection of communities of practice

Abstract: This study examines the development and ongoing activities of a collaboration between an urban elementary school and a nearby aquarium. Although the benefits of such collaborations in support of science education are touted by numerous national organizations, the pathway to creating a successful relationship between these two different institutions, with inherently different cultures, is less well documented. Using the theoretical framework of communities of practice (E. Wenger, 1998), a better understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 30 publications
0
27
0
3
Order By: Relevance
“…There was specific comment from 14 of the interviewees about problems of communication across the boundary between school and the community organisation. This should not be a surprise as other studies have identified communication as a significant issue (Kisiel, 2010;Rennie, 2012). Under the general heading of communication, we could identify several specific issues.…”
Section: Communicationmentioning
confidence: 78%
See 3 more Smart Citations
“…There was specific comment from 14 of the interviewees about problems of communication across the boundary between school and the community organisation. This should not be a surprise as other studies have identified communication as a significant issue (Kisiel, 2010;Rennie, 2012). Under the general heading of communication, we could identify several specific issues.…”
Section: Communicationmentioning
confidence: 78%
“…First, while there is a great deal of diversity in the collaborations that exist (Slater & Ravid, 2010; from large scale operations such as Australia's Scientists in Schools, see for example Howitt & Rennie, 2009;Rennie, 2012; to smaller scale collaborations, see for example, Kisiel, 2010), there are not many studies in which the researchers explore more than one type of arrangement. There is thus a need for research studies which explore the issues around such activity across a range of types of collaboration.…”
Section: Research Into School-community Collaborationsmentioning
confidence: 98%
See 2 more Smart Citations
“…En esta categoría se incluyen algunos artículos cuyo objetivo era realizar un estudio de las investigaciones que tenían como objeto la enseñanza y el aprendizaje en museos (Martín, 2004;Kay et al 2009;Kisiel, 2009;Boehme et al 1997).…”
Section: Investigaciones Desarrolladas En Torno a Los Ambientes Inforunclassified